Framing the triple bottom line approach: Direct and mediation effects between economic, social and environmental elements. (1st October 2018) - Svensson, Göran; Ferro, Carlos; Høgevold, Nils; Padin, Carmen; Carlos Sosa Varela, Juan; Sarstedt, Marko
Abstract: Conflicting relationships between the economic, social and environmental elements of business sustainability, which are also referred to as the Triple Bottom Line (TBL), characterise today's business environment. While the TBL has recently attracted considerable research, not a single study has empirically tested the direct and indirect effects between the TBL elements. By addressing this gap in research, this study sheds light on the structural properties focusing on the direct effects and the indirect effect (i.e., mediation) between the TBL elements. The results of two cross-industrial studies in Norway and Spain indicate that the TBL's economic element has a direct effect on the environmental element, with the social element mediating this effect. The results reported here offer long-needed empirical insights into the interplay between the three TBL elements, which have important implications for research and practice. Graphical abstract: